CREDIT MARKET DEVELOPMENT DIRECTIONS IN MODERN UKRAINIAN CONDITIONS: Array - Verbytska, V.; Bredikhin, V. (Municipal economy of cities. Series: «Economy science», 2020)
The article is devoted to the review of the current state, problems and directions of improving the activities of banking and microfinance organizations (MFIs) in the lending market. The methods of attracting customers to obtain loans are analyzed and the international experience of banking and non-banking organizations in the field of lending to the population is investigated. It was concluded that the economic development of the state not only implies, but also requires the development of market lending mechanisms that can not only provide banking institutions with a profit, but also ensure stable economic growth. In addition, it should be noted that there is a different focus on research in this area, as well as the lack of a unified approach to determining directions for improving lending competitiveness, and the mismatch between the chosen strategies for the real situation that has developed in Ukraine. It has been established that the largest share in the lending market belongs to consumer loans, classic loans to individuals, when borrowed funds are taken to pay for various necessities of life. At the same time, the presence of negative trends and factors affecting the stability and stability of the banking system has been identified, which makes it necessary to study and constantly monitor the status of consumer lending in order to identify potential problems. It is stated that at present, to expand the client market of credit institutions, it is necessary not only to expand the range of items provided under credit, but also to disseminate information and promote these services on the market. The main ways to attract customers to obtain loans and events that are actively used by credit institutions around the world are identified. The opinion of leading experts on the need to address a number of tasks to ensure the rights and legitimate interests of borrowers in the field of consumer lending is recorded. The principles of building a hierarchical system for working with loan applications are outlined.